Late Mesozoic marine Antarctic fishes: future perspectives based on the newly collections recovered in the Ameghino and Lopez de Bertodano Formations - Gouiric Cavalli, Soledad (2017)
Nowadays, notothenioids are the teleostean group that dominates marine Antarctic waters. However, during the Mesozoic a diverse ichthyofauna inhabited the sea that surrounded Antarctic. We present the preliminary results of the last two Argentinian Antarctic field expedition to the Late Jurassic of Antactic Peninsula (Longing Gape) and Cretaceous-Paleogene of Seymour (=Marambio) Island. The fish material recovered is extremely abundant and their further detailed study may provide significant clues into the taxonomy and paleobiogeography of the mesozoic antactic ichthyofaúnas.